Aplikasi Android Mengenal Tata Surya Berbasis Augmented Reality Sebagai Media Belajar Interaktif Siswa Sekolah Dasar - Rakhmat, Galih Ashari (Forum Kerjasama Pendidikan Tinggi, 2020)
The use of Android-based smartphones is currently increasing rapidly. This makes application developers compete to create various applications. Augmented Reality (AR) is an environment that inserts 3D virtual objects into a real environment. AR is a visualization technology that is currently being developed in several fields. Augmented Reality application in the field of education developed in this study is to discuss the solar system for elementary school students. By presenting a good application content, children's imagination will develop positively. Many media explain about the solar system, such as books and videos. However, the development of Augmented Reality-based media is expected to provide its own insights for students. This research has successfully developed a prototype of a product or media in the form of a book that can be interacted with the AR application on an Android smartphone. The discussion in this study will focus on the application side designed, not on the interactive book design side. Regarding the interactive book media, visual displays of books which have been developed. Application testing has been done by directly interacting with students at the elementary school level, then they respond to the questionnaire. The results of these tests are, the level of usability of the application gets a good response and is easy for use by elementary school students